Retinal topography and microhabitat diversity in a group of dragon lizards. Issue 4 (17th October 2019) - Nagloo, Nicolas; Coimbra, João Paulo; Hoops, Daniel; Hart, Nathan S.; Collin, Shaun P.; Hemmi, Jan M.
Abstract: The well‐studied phylogeny and ecology of dragon lizards and their range of visually mediated behaviors provide an opportunity to examine the factors that shape retinal organization. Dragon lizards consist of three evolutionarily stable groups based on their shelter type, including burrows, shrubs, and rocks. This allows us to test whether microhabitat changes are reflected in their retinal organization. We examined the retinae of three burrowing species ( Ctenophorus pictus, C. gibba, and C. nuchalis ), and three species that shelter in rock crevices ( C. ornatus, C. decresii, and C. vadnappa ). We used design‐based stereology to sample both the photoreceptor array and neurons within the retinal ganglion cell layer to estimate areas specialized for acute vision. All species had two retinal specializations mediating enhanced spatial acuity: a fovea in the retinal center and a visual streak across the retinal equator. Furthermore, all species featured a dorsoventrally asymmetric photoreceptor distribution with higher photoreceptor densities in the ventral retina. This dorsoventral asymmetry may provide greater spatial summation of visual information in the dorsal visual field. Burrow‐dwelling species had significantly larger eyes, higher total numbers of retinal cells, higher photoreceptor densities in the ventral retina, and higher spatial resolving power than rock‐dwelling species. C. pictus, a secondary burrow‐dwelling species, was the only species that changed burrow usage over evolutionary time, and its retinal organization revealed features more similar to rock‐dwelling species than other burrow‐dwelling species. This suggests that phylogeny may play a substantial role in shaping retinal organization in Ctenophorus species compared to microhabitat occupation. Abstract : We reveal two highly conserved retinal specializations among Ctenophorus lizards including a horizontal streak at the retinal equator and fovea at the retinal center. In addition, higher photoreceptor densities in the ventral retina create a dorsoventral asymmetry of varying degrees across species. Results presented here suggest that phylogeny plays a significant role in the retinal organization of Ctenophorus species.